Associations of California's Tobacco 21 Minimum Sales Age Law with Tobacco Use Among Sexual Minority Adolescents: A Trends Analysis. Issue 11 (23rd May 2022) - García-Ramírez, Grisel; Islam, Sabrina; Wharton, Mary K; Grube, Joel W
Abstract: Introduction: In 2016, California enacted a law (T21) prohibiting tobacco product sales to individuals under 21 years of age. Given tobacco use disparities among sexual minority (SM) youth, this study investigated whether California's T21 law was differentially associated with changes in tobacco use for SM and non-SM adolescents. Aims and Methods: Secondary analyses of California Healthy Kids Survey data from 2013–2014 to 2018–2019 for 7th, 9th, and 11th graders ( N = 2 229 401). Results: Multilevel mixed-effects logistic regression analyses showed that SM students were more likely than non-SM students to report past-30-day and lifetime cigarette (odds ratio (OR) = 2.47; OR = 2.37), e-cigarette (OR = 1.21; OR = 1.10), smokeless tobacco use (OR = 1.95; OR = 1.56), and use of any tobacco product (OR = 1.94; OR = 1.61). Among SM youth, T21 was associated with significant reductions in lifetime e-cigarette use (OR = 0.66), and lifetime use of any tobacco products (OR = 0.75). These decreases generally were greater than or equivalent to those observed for non-SM youth. For 30-day e-cigarette and any tobacco use, SM youth showed no significant increases, whereas non-SM youth showed significant increases (OR = 1.06; OR = 1.11) following T21. T21 was associated with smaller increases in lifetime cigarette use (OR = 1.34), and larger increases for past-30-day and lifetime smokeless tobacco use (OR = 1.34; OR = 1.28) among SM students, to those observed for non-SM students. Conclusions: California's T21 policy may help reduce tobacco use disparities among SM students who are more at risk for tobacco use than their non-SM peers. Implications: Research on associations of T21 laws with tobacco use among sexual minority (SM) adolescents is lacking. The potential for unintended consequences of T21 for these adolescents raises concerns about increased health disparities. Importantly, our study generally found California's T21 was associated with reductions in tobacco use among SM students that were equivalent to or greater than those for non-SM students. Future research should investigate whether T21 laws and similar policies have differential effects for other marginalized groups and, if so, identify mechanisms that can be targeted in prevention efforts.